Rancang Bangun Sistem Pendukung Keputusan Penerimaan Dana Bansos Covid-19 Dengan ODOO ERP - Winda Yohanna Siahaan; Tukino Tukino (LPPM Universitas Putera Batam, 2022)
Information technology is one of the needs of the people, both in the place of individuals and groups, both public and private; ) in large quantities in large quantities. For a certain time, the company provides assistance to employees, especially in the current situation, the company regularly provides social assistance to employees who need it, so the company requires decision makers to use computer-coordinated procedures. Because social assistance must be distributed appropriately and quickly, there is a need for some kind of a decision support system to receive social assistance, using the method of comparing employee profiles with recipient criteria, especially the profile compliance method. The research method is called waterfall method, the first step is needs of analysis, design, code generation, testing, and maintenance. The results obtained are the design of the Social Assistance Fund receipt system using the profile matching method, so that the resulting information system assists decision makers in distributing social assistance funds quickly and accurately to employees. consists of requirements analysis, design, code generation, testing, and maintenance. The results obtained are the design of the Social Assistance Fund receipt system using the profile matching method, and hoping that the result information system assists decision makers in distributing social assistance funds quickly and accurately to employees.